The mechanism behind the selection of two different cleavage sites in NAG-NAM polymers. (2017) - Mihelič, M.; Vlahoviček-Kahlina, K.; Renko, M.; Mesnage, S.; Doberšek, A.; Taler-Verčič, A.; Jakas, A.; Turk, D.
No abstract available